Faktor-Faktor yang Memengaruhi Kesediaan Berinvestasi Saham (Studi Kasus pada Galeri Bursa Efek Indonesia Politeknik Negeri Samarinda dan Universitas Muhammadiyah Kalimantan Timur) - Diyah Permana; Sigit Hartoko; Indri Rusdiana Dewi (Jurnal EKSIS, 2023)
This study aims to determine the effect of financial literacy, financial experience, and overconfidence on the willingness to invest in shares of Samarinda State Polytechnic students and Muhammadiyah University, East Kalimantan. The analytical tool used in this study is multiple linear regression analysis. The results of multiple linear regression, the regression equation is obtained as follows Y = 2.488 + 0.202X1 + 0.184X2 + 0.168 X3 + e namely financial literacy of 0.202, financial experience of 0.184, and overconfidence of 0.168. Research shows that partially the variables of financial literacy and overconfidence both have a positive and significant effect on the willingness to invest in stocks in Samarinda State Polytechnic students and Muhammadiyha University, East Kalimantan, while financial experience has a positive and not significant effect on the willingness to invest in stocks in Samarinda State Polytechnic students. and Muhammadiyha University, East Kalimantan. Simultaneously the variables of financial literacy, financial experience, and overconfidence have a positive and significant effect on the willingness to invest in shares of Samarinda State Polytechnic students and Muhammadiyha University, East Kalimantan. Keywords: financial literacy, financial experience, overconfidence, willingness to invest in stocks